Charge distribution in homonuclear bonds: A semiempirical modeling. Issue 8 (20th December 2013) - Speranza, Giorgio; Minati, Luca
<x xml:space="preserve">Abstract</x> Atoms characterized by nonequivalent electronegativities form chemical bonds by exchanging electrical charge. The fraction of charge exchanged is dictated by the electronegativity differences among the system atoms. In the electronegativity equalization method, the charge distribution is estimated by forcing the system to relax to a common chemical potential, which corresponds to its configuration of energy minimum. By definition, this method cannot be applied to homonuclear bonds. A model is proposed to estimate the charge shared in molecular orbitals of homonuclear molecules. The model expands upon the electronegativity equalization method by adding formalism to describe the spin coupling characteristic of homonuclear bonds. Results are in excellent agreement with other quantum mechanical estimations of the charge distributions. © 2013 Wiley Periodicals, Inc.